STATUS KEPEMILIKAN ATAS SATUAN RUMAH SUSUN - Anak Agung Ngurah Arya Winata; I Nengah Suharta (Kertha Negara : Journal Ilmu Hukum, 2014)
Property rights of the ownership over the land unit of flats, which is built up on land of building rights over the management rights, where the terms of the extension of ownership rights over the land have to obtain approval of the extension by the holder of management rights. The problem is how the status of ownership of property rights over units if flats, if doesn’t have obtain approval of the extension. This legal research is a normative research through the study of legislation the act No. 16 of 1985 jo. The act No. 20 of 2011 and government regulation No. 4 of 1988 about the flats. The conclusion of this research is not explained about the status of ownership the property rights over the units of flats, if doesn’t have approval of the extension which cause nullification of a building rights over the land of management rights.